2011
DOI: 10.1016/j.rasd.2010.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Top-down and bottom-up visual information processing of non-social stimuli in high-functioning autism spectrum disorder

Abstract: Objective: Individuals with high functioning autism spectrum disorder (HF-ASD) often show superior performance in simple visual tasks, despite difficulties in the perception of socially important information such as facial expression. The neural basis of visual perception abnormalities associated with HF-ASD is currently unclear. We sought to elucidate the functioning of bottom-up and top-down visual information processing in HF-ASD using event-related potentials (ERPs). Methods: Eleven adults with HF-ASD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 72 publications
5
33
2
Order By: Relevance
“…In spite of that, a dissociation between the sensory processing, the deviance detection, and the behavioral response was observed between controls and patients with ASD. Whereas studies in other disorders reported lower amplitudes or longer latencies of the early sensory response for standard or deviant stimuli, deviance detection was either similar (Maekawa et al, 2011) or even earlier (Clery, Andersson, et al, 2013; in patients with ASD than that in controls. Such dissociation suggests 1) sensory impairment, and 2) disorganization of higher information processing in patients with ADS (Fig.…”
Section: Developmental Disorderscontrasting
confidence: 60%
See 3 more Smart Citations
“…In spite of that, a dissociation between the sensory processing, the deviance detection, and the behavioral response was observed between controls and patients with ASD. Whereas studies in other disorders reported lower amplitudes or longer latencies of the early sensory response for standard or deviant stimuli, deviance detection was either similar (Maekawa et al, 2011) or even earlier (Clery, Andersson, et al, 2013; in patients with ASD than that in controls. Such dissociation suggests 1) sensory impairment, and 2) disorganization of higher information processing in patients with ADS (Fig.…”
Section: Developmental Disorderscontrasting
confidence: 60%
“…Whereas Maekawa et al (2011) did not find any vMMN difference between patients and controls, found that deviance processing is distinct in controls and the ASD patients, and in the latter group it resembles novelty detection. Gayle et al (2012) described a relationship between autistic quotient and the deviance processing of socially relevant stimuli in healthy subjects.…”
Section: Developmental Disordersmentioning
confidence: 59%
See 2 more Smart Citations
“…Some studies have already begun to investigate MSI in ASD using neuroimaging methods (e.g., EEG, fMRI) but additional research is needed to fully understand the neural mechanisms that underlie multisensory integration in ASD (Brandwein et al 2013;Maekawa et al 2011;Magnée et al 2008).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%